1997
DOI: 10.3168/jds.s0022-0302(97)76243-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Bacteriological Cure During Lactation After Therapy for Subclinical Mastitis Caused by Staphylococcus aureus

Abstract: The objective of this study was to determine the factors that were associated with the cure of subclinical mastitis caused by Staphylococcus aureus treated during lactation. One hundred forty-three quarters that were infected with S. aureus were available from a number of treatment trials. Analysis of these data showed that the most important factors associated with cure were age of the cow, somatic cell count at the time of treatment, presence of the infection in the front quarters, and stage of lactation. Ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
101
5
17

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(138 citation statements)
references
References 8 publications
8
101
5
17
Order By: Relevance
“…Penicillin resistance is generally associated with decreased Staph. aureus cure rates (Sol et al, 1997;Barkema et al, 2006), but a relatively high cure rate for penicillin-resistant strains was observed in our study on early treatment of Staph. aureus mastitis (van den Borne et al, 2010).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Penicillin resistance is generally associated with decreased Staph. aureus cure rates (Sol et al, 1997;Barkema et al, 2006), but a relatively high cure rate for penicillin-resistant strains was observed in our study on early treatment of Staph. aureus mastitis (van den Borne et al, 2010).…”
Section: Discussionmentioning
confidence: 90%
“…Our results suggest that determination of Staph. aureus host adaptation has value in predicting bacteriological cure after antimicrobial treatment during lactation and could be used to guide treatment and management decisions in dairy practice, together with information on cow characteristics (Sol et al, 1997;Deluyker et al, 2005;Barkema et al, 2006;Sandgren et al, 2008). Specifically, to achieve good probabilities of cure, treatment duration for bovine-associated strains may need to be longer compared with that for nonbovine-associated strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such residues may be detrimental to the manufacture of certain cultured milk products, and antibiotic use in animal production contributes to microbe resistance (Belschner et al 1996;Kirk et al 2002;Oliver et al 1992). A wide range of alternatives to antibiotics have emerged as a result of their ban (organic acids, probiotics, herb extracts, and others), of which passive immunization with antibodies is an approach with great potential due to its high specificity (Sol et al 1997). …”
Section: Introductionmentioning
confidence: 99%
“…The initial estimate for the parameter value for τ is 0n01 day −" . This is based on a mean time to detection of 60 days, and an estimated cure rate after treatment of 60 % [13]. This would represent a realistic but aggressive treatment policy.…”
Section: Controlmentioning
confidence: 99%